Dār al-islām/dār al-ḥarb: territories, people, identities - Calasso, Giovanna; Lancioni, Giuliano (Studies in Islamic law and society, 2017)
Concepts, words, historical realities of a "classical" dichotomy / Giovanna Calasso -- Constructing and deconstructing the Dar al-Islam / Dar al-ḥarb opposition between sources and studies / Giovanna Calasso --The dmssing dar on collocations in classical Arabic dictionaries / Giuliano Lancioni --The perception of the others, Rum and Franks (tenth-twelfth centuries) / Yaacov Lev -- Some observations on Dar al-ḥarb / Dar al-Islam in the Imami context / Biancamaria Scarcia Amoretti -- Naming the enemy's land: definitions of dar al-ḥarb in Ibn al-Mubarak's Kitab al-Jihad / Roberta Denaro --6 Dar al-Islam / dar al-ḥarb in the Tafsir by Ibn Jarir al-Tabari and in early traditions / Roberto Tottoli -- The Qurʼanic foundations of the Dar al-Islam / dar al-ḥarb dichotomy: an unusual hypothesis / Raoul Villano -- Dar al-Islam et dar al-ḥarb : quelques reflexions a propos de la geographie theologico-politique sunnite classique, en regard du Kitab al-Muhadhdhab d'Abu Isḥaq al-Sirazi (m. 476/1083) / Eric Chaumont = An unknown minority between the Dar al-ḥarb and the Dar al-Islam / Francisco Apellaniz -- Some observations on the concept of dar al-jahd in the Ottoman context (XVI-XVII c.) / Nicola Melis -- Some Notes on Dar al-ḥarb in early al-Andalus / Maribel Fierro and Luis Molina -- Les emirs d'Iran nord-oriental face aux steppes turques (IXe-XIe siecle) : entre legitimation, confrontation et cohabitation / Camille Rhone -- Dar al-Islam ou Bilad al-rum ? Le cas de l'Anatolie turque au Moyen-Age / Michel Balivet -- Une appartenance controversee : trois moments dans le debat autour du statut du bilad al-Sudan / Francesco Zappa --Faith as territory: Dar al-Islam and Dar al-ḥarb in modern Shiʻi sufism / Alessandro Cancian -- Dar al-Islam and Darul Islam: from political ideal to territorial reality / Chiara Formichi -- Dar al-Islam and Dar al-ḥarb in modern Indian Muslim thought / Yohanan Friedmann -- Better barr al-jadw than dar al-ḥarb: some considerations about eighteenth-century Magribi chronicles / Antonino Pellitteri -- Muḥammad Bayram's Risala fi dar al-ḥarb wa-suknaha: a modern reinterpretation of living in Dar al-ḥarb / Francesca Romana Romani and Eleonora Di Vincenzo -- Concluding remarks: the terminological array / Giuliano Lancioni